Propuesta de políticas e indicadores de gestión ambiental aplicado a las empresas del sector textil, prendas de vestir y Cuero Fashion Lana Cía. Ltda. - Arias Vega, Jorge Anibal (2015)
The importance of conserving the environment every time is more significant due to the environmental impacts than they are generated, it is in and of itself that the conscience ecological debit side to be born of each one of people, however this care should also lead it the big industries being every day more responsible with the natural resources when manufacturing a well or to lend a service. This document is based in proposing political environmental that help to the development of good practical environmental in the company Fashion Lana Co. Ltda., belonging to the textile sector, you are captivated of dressing and leather, facilitating the necessary information to make possible east work, allowing to know the productive process of the company and to identify possible environmental impacts that affect to the water, air, floor, residuals and resources. The politicians environmental proposals will be for benefit and help of Fashion Lana Co. Ltda., reaffirming their commitment with the environment when carrying out the production process, fulfilling the requirements of norms, laws and ordinances that are established, and also proposing indicators of environmental administration to measure the execution of the politicians.